Affordances of community-oriented praxis in teacher education: a configurative review - Kitooke, Amoni; Mahon, Kathleen (Frontiers in Education, 2024)
This configurative review explores how nurturing and enacting a community-oriented praxis (COP) in teacher education can enhance teacher candidates' preparedness for teaching roles whilst addressing some broader educational and societal concerns. Here, CoP is defined as practices that consider, connect with, and draw on local community strengths, needs, and aspirations for the good of individuals, communities, and society more broadly. We review 31 cases in 37 articles on explicitly community-oriented teacher education (COTE) initiatives from nine country contexts where teacher educators, school-based mentors, and members of local communities collaboratively facilitate the learning experiences of participants in teacher education (i.e. teacher candidates). An analysis of the motivations, processes, and outcomes of the initiatives in the COTE cases highlights benefits such as developing teacher candidates' pedagogical content knowledge and research competence; fostering social justice consciousness and critical action; and facilitating the sustainable recruitment and retention of teachers especially in marginalised contexts. Implications and possible directions for teacher education are discussed.